Mathematical Modeling Of The Quality Indicators Of TwoLayer Knitted Fabrics Obtained On Flat Two-Needle Knitting Machines With The Needles Placed In A Rubber Arrangement - Z.J. Borotov; K.M. Khalikov; N.M. Musaev; M.M. Mukimov; B.M.Qurbanov (Zien Journals, 2023)
In the article presents the results of mathematical modeling of the quality indicators of double-layer knitted fabrics on double-bed flat knitting machines and the law of the influence of the structure of knitted fabric on the consumption of weed is determined
Keywords: double-layer; knitting; quality